2001
DOI: 10.1002/1529-0131(200104)44:4<956::aid-anr153>3.3.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Development and characteristics of a synovial‐like interface membrane around cemented tibial hemiarthroplasties in a novel rat model of aseptic prosthesis loosening

Abstract: Objective. Aseptic prosthesis loosening (APL) is related to the formation and aggressive growth of a synovial-like interface membrane (SLIM) between prosthesis and bone. However, investigation of the early phases of SLIM development in humans presents major difficulties. This study was undertaken to develop and characterize the usefulness of a novel animal model of APL that is based on an established model of defined exercise in a running wheel by Wistar rats that have been subjected to intracranial self-stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 6 publications
2
25
0
Order By: Relevance
“…This shortcoming is also true in the animal models, as demonstrated by a modified rat model that incorporated a running wheel for 2 h/day for 5 days/week. 64 Despite…”
Section: Animal Modelsmentioning
confidence: 99%
“…This shortcoming is also true in the animal models, as demonstrated by a modified rat model that incorporated a running wheel for 2 h/day for 5 days/week. 64 Despite…”
Section: Animal Modelsmentioning
confidence: 99%
“…3 4 A major drawback of TJA is so called "aseptic loosening". 5 The aetiology of this condition is blamed on two major factors (a) particles of polyethylene (PE), bone cement, ceramics, or metal resulting from wear (wear particles) stimulate macrophages to produce resorption stimulating factors and thus lead to periprosthetic osteolysis; [6][7][8][9][10] or (b) lack of initial stability, which is considered essential for osseointegration. 11 12 Apart from aseptic loosening, loosening may be induced by periprosthetic infection (septic loosening), which originates from minimal bacterial contamination during surgery or from bacteria that reach the prosthesis via the bloodstream or lymphatic system.…”
mentioning
confidence: 99%
“…This is also of interest for aseptic prosthesis loosening, because it has been demonstrated that the inflamed synovial membrane in RA and the synovium-like interface membrane in aseptic prosthesis loosening share some important features (1,11), and several lines of evidence suggest that fibroblasts derived from this membrane exhibit an aggressive phenotype that is similar to that of RA FLS (12,13). Therefore, we set out to study the apoptotic response of prosthesis-loosening FLS in comparison with that of RA FLS and investigated whether posttranslational modifications by SUMO-1 (in a manner similar to that in RA FLS) contributes to the resistance of prosthesis-loosening FLS to programmed cell death.…”
Section: Discussionmentioning
confidence: 99%